DEVELOPING STUDENTS' PROFESSIONALLY-ORIENTED COMMUNICATIVE COMPETENCE THROUGH THE RUSSIAN LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
In the modern educational environment, developing professionally-oriented communicative competence has become one of the main tasks of higher education. The rapid development of international cooperation, digital communications, and professional mobility requires graduates not only to possess specialized knowledge but also to possess effective communication skills in various professional contexts. Russian, as the language of science, technology, business, and intercultural communication in many countries, serves as an important tool for developing students' professional communication skills. This article examines the concept of professionally oriented communicative competence, analyzes the role of the Russian language in its development, and explores pedagogical methods and strategies that contribute to the development of effective professional communication skills in students.